PENINGKATAN MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA KELAS II SMPN 2 RAHAN PESISIR DALAM PELAJARAN BAHASA INDONESIA MELALUI MODEL PEMBELAJARAN MIND MAPPING - Riska Mayeni; Yanti Nazmai Ekaputri; Titik Hardewi Yani; Intan Dwi Rahayu; Sefrinal Sefrinal (STKIP Pesisir Selatan, 2022)
This research is motivated by low student motivation and learning outcomes. This study aims to: (1) determine the application of the mind mapping model, (2) increase learning motivation in Indonesian subjects through the application of mind mapping models, (3) improve Indonesian learning outcomes through the application of a mind mapping model. This type of research is CAR which consists of two cycles, each cycle consists of planning, implementation, observation and reflection. The research subjects were students of class IISMPN 2 Coastal Domain for the 2021/2022 academic year which opened 10 students. The object of the research is the improvement of learning motivation and learning outcomes in Indonesian subjects about news texts. Data collection techniques obtained by observation, questionnaires and written tests. Data analysis in this study used quantitative and qualitative descriptive analysis. The results of the study showed the application of the mind mapping model to increase students' learning motivation. in the second cycle increased to 81.34 (high). The application of the mind mapping model can improve student learning outcomes of SMPN 2 Ranah Pesisir. This can be seen in the increase in the average test score in the initial conditions of 71.45 with the presentation of completeness (68.18%) increasing to 76.3 with the presentation of completeness (88.89%) in the first cycle, then to 81 with the presentation of learning completeness. (92.55%) in cycle II.